The Study of Fear of Crime and Its Impact on Fans' Abnormal Behavior at Stadiums (A Case Study of Football Fans at Fooladshahr Stadium in Isfahan, Iran) - Masoud Naderian Jahromi; Elham Akhavan (Shahid Bahonar University of Kerman, 2021)
The overall purpose of this study was to perform a descriptive research on fear of crime, its related individual factors and sports environments, as well as the occurrence of inappropriate behavior by fans at stadiums. The research tool was a researcher-developed questionnaire that was found to be valid and reliable. 315 football fans completed the questionnaires at Fooladshahr Stadium in Isfahan, Iran in the second half of 2019. The results showed that the variables of age, level of education and marital status had a significant relationship with fear of crime. Among the teens, 13 to 17 years old, fear of crime was less than the youth while among the youth, it was more considerable than adults. Other individual variables (ethnicity, parents' income and family cultural environment) did not have a significant relationship with fear of crime. Variables related to sports environments, group of friends, rudeness at stadiums, the quality of sports environments, extreme attachment to a team, and crime perception in sports environments are also significantly related to fear of crime.  This study emphasizes the need for special attention of sports and security officials to the strict implementation of laws, as well as updating the laws in line with developments and training of fans behavior at stadiums.